Determination Of Factors That Influence Employee Performance - Lestarina, Ayu; Safitri, Handayu (IJBLE Scientific Publications Community Inc., 2024)
The objective of this research is to examine empirical data demonstrating how a leader's style affects work discipline and employee performance. This research employed a census methodology, using 150 employees of PT. SurajBraja Cukup Rupiah as respondents, representing the entire population. Structural Equation Modeling (SEM) is the data analysis method used. The findings demonstrated that work discipline and employee performance were positively and significantly influenced by leadership style. While employee performance is not directly impacted by a leader's style, it is indirectly affected. These findings demonstrate that increased work discipline and staff performance follow from a stronger leadership style. Optimal performance can be improved by firm leadership exercising more discipline in the workplace.